Nordeste e sua disponibilidade para o consumo sustentável através de energias renováveis - Santos, Wiliam Souza (2015)
The world after industrial revolution began to require greater demand for energy resources, but most of it is exhaustible and pollute the environment. On the face of it, it opened the way for the emergence of so-called renewable energy, clean (not pollute directly). The theme that involves sustainability and renewable energy is currently very discussed and this article has been prepared in order to show what the Brazilian Northeast has and can offer in terms of natural resources. That region has as main resources: water, wind, sun and biomass. And through these is possible to generate clean energy through hydroelectric plants, wind farms, solar panels and combustion.